Perioperative Management and Preemptive ECMO Cannulation of a Parturient with Cystic Fibrosis Undergoing Cesarean Delivery - Thais Franklin Dos Santos; Andrea Rabassa; Oscar Aljure; Reine Zbeidy (Case Reports in Anesthesiology)
Physiologic changes of pregnancy and cystic fibrosis pathology provide a unique set of circumstances. Pulmonary disease accounts for over 90% of the morbidity and mortality of patients with cystic fibrosis. These abnormalities create anesthetic challenges due to multiple organ systems being affected including the respiratory, gastrointestinal, cardiovascular, and genitourinary tracts, where patients present with chronic respiratory failure, pancreatic insufficiency, poor nutrition, and cardiac manifestations. We present the perianesthetic management of a parturient with cystic fibrosis who successfully underwent preterm cesarean delivery under neuraxial anesthesia with preemptive bilateral femoral venous sheaths placed for potential extracorporeal membrane oxygenation (ECMO) initiation.